Therapeutic genome editing with engineered nucleases - Haas, Simone A.; Dettmer, Viviane; Cathomen, Toni (Hämostaseologie, 2017)
Targeted genome editing with designer nucleases, such as zinc finger nucleases, TALE nucleases, and CRISPR-Cas nucleases, has heralded a new era in gene therapy. Genetic disorders, which have not been amenable to conventional gene-addition-type gene therapy approaches, such as disorders with dominant inheritance or diseases caused by mutations in tightly regulated genes, can now be treated by precise genome surgery. Moreover, engineered nucleases enable novel genetic interventions to fight infectious diseases or to improve cancer immunotherapies. Here, we review the development of the different classes of programmable nucleases, discuss the challenges and improvements in translating gene editing into clinical use, and give an outlook on what applications can expect to enter the clinic in the near future.
Keywords: clinical application; clinical trial; designer nuclease; gene editing; gene therapy; genetic disorder